Peran Gramatika Arab dalam Menjamin Keakuratan Tafsir dalam Ulumul Qur`an - Muh Ikraam Sayyid Amir; Achmad Abubakar; Hamka Ilyas (Lathaif)
The Qur'an, as the holy book of Islam, was revealed in Arabic a language with a complex grammatical structure. This study aims to examine the crucial role of Arabic grammar in ensuring the accuracy of Qur'anic interpretation within the framework of Ulumul Qur’an (Qur’anic sciences). The methodology employed is a qualitative approach through literature review of both classical and contemporary tafsir works, as well as Arabic linguistic sources. The findings indicate that Arabic grammar is not merely a technical tool, but also serves as an epistemological foundation for scholarly and accountable interpretation. These findings underscore the urgency of strengthening Arabic grammar education in Islamic institutions to produce interpreters (mufassir) who can understand the sacred text both contextually and profoundly. The study also recommends the integration of linguistic approaches in tafsir to address the challenges of the post-truth era and multicultural societies.